Taxonomic identity of Alysicarpus pokleanus (Papilionoideae: Leguminosae) - Tiwari, Arjun Prasad (Phytotaxa, 2020)
The taxonomic identity of recently described Alysicarpus pokleanus is resolved here as synonym of A. hamosus. The image of type specimen of A. hamosus and A. pokleanus along with colour photographs of fresh collection of A. hamosus from the type locality are also provided. Further, the inconsistencies in the protologue of A. pokleanus are discussed in the present paper.